Finite element analysis of expansion-matched submounts for high-power laser diodes packaging. (June 2016) - Yuxi 倪, Ni 羽茜; Xiaoyu 马, Ma 骁宇; Hongqi 井, Jing 红旗; Suping 刘, Liu 素平
Abstract: In order to improve the output power and increase the lifetime of laser diodes, expansion-matched submounts were investigated by finite element analysis. The submount was designed as sandwiched structure. By varying the vertical structure and material of the middle layer, the thermal expansion behavior on the mounting surface was simulated to obtain the expansion-matched design. In addition, the thermal performance of laser diodes packaged by different submounts was compared. The numerical results showed that, changing the thickness ratio of surface copper to middle layer will lead the stress and junction temperature to the opposite direction. Thus compromise needs to be made in the design of the vertical structure. In addition, the silicon carbide (SiC) is the most promising material candidate for the middle layer among the materials discussed in this paper. The simulated results were aimed at providing guidance for the optimal design of sandwich-structure submounts.